Preoperative progressive pneumoperitoneum for a giant incisional hernia: report of a case with a rare complication - Nunes, Vinicius Rodrigues Taranto; Barbuto, Rafael Calvão; Cunha-Melo, José Renan; Pastore Neto, Mario; Machado, Carla Jorge; Lourenço, Galileu Chagas; Pena, Guilherme Nogueira; Marino, Marcello Fonseca; Farias, David Silveira; Toledo, Ingrid Bremer (Revista da Faculdade de Ciências Médicas de Sorocaba, 2018)
In patients with giant incisional hernias, many anatomical and physiological changes turn hernia repair into quite a challenge. The possibility of developing complications as abdominal compartment syndrome after hernioplasty has prompted surgeons to seek for technical options. A tempting alternative is to induce progressive preoperative pneumoperitoneum (PPP) aiming to adapt the organism to an increase in the abdominal content. We describe the case of a patient with giant incisional hernia submitted to PPP. The patient complicated with a very symptomatic pneumomediastinum. Despite being frequently well tolerated, it is important to make a point that the induction of PPP may result in severe complications.